Wild ungulates and shrub control interact to restore herbaceous vegetation in shrub-encroached mesic grassland of South Africa - Mndela, Mthunzi; Barrett, Alan S.; Brown, Leslie R. (Frontiers in Ecology and Evolution, 2023)
Shrub encroachment threatens grassland ecosystem services including amongst others herbaceous plant diversity, productivity, and overall grazing capacity. Hence, various shrub control methods including mechanical removal and herbicides are applied to restore herbaceous vegetation. However, the knowledge regarding the outcomes of integrated shrub management on herbaceous vegetation is limited. We investigated herbaceous vegetation responses after 7 years following the integration of shrub control and herbivory at Telperion nature reserve, Mpumalanga Province, South Africa. In a split-plot experiment with four enclosures and non-enclosures as main plots, we randomly assigned each of the following treatments: 1) foliar Metsulfuron-methyl herbicide, 2) 50% mechanical shrub removal, 3) 100% removal, and 4) no removal (untreated controls) in four 4x4 m subplots in each main plot. A one-off Seriphium plumosum removal and the application of species-specific herbicide was conducted in 2015. Shrub control by herbivory interaction was significant (P<0.05) for herbaceous canopy cover, basal cover, density, and species richness. The effects of herbivory were significant (P<0.05) in the 50% removal treatment, increasing herbaceous plant diversity, density, and richness to the same level as 100% removal and herbicide treatments.In enclosures, however, the 50% shrub removal treatment attained relatively low herbaceous plant cover, density, species diversity and richness compared to the herbicide treatment.Overall, this study revealed that herbivory and shrub control interact to facilitate herbaceous vegetation restoration, with 50% shrub removal by herbivory combination showing a potential for management of S. plumosum encroached grasslands.